Intertemporal income shifting and the taxation of business owner-managers - Helen Miller; Thomas Pope; Kate Smith (Institute for Fiscal Studies (IFS), 2021)
We use newly linked tax records to show that the large responses of UK company owner-managers to personal taxes are due to intertemporal income shifting and not to reductions in real business activity. Around half of this shifting is short-term and helps prevent volatile incomes being taxed more heavily under progressive personal taxes. The remainder reflects systemic profit retention over long periods to take advantage of lower tax rates, including preferential treatment of capital gains. We find no evidence that this tax-induced retention increases business investment. It does, however, substantially reduce the tax revenue raised from high income business owners.
Keywords: H30; H24; H26; D25; 330; income shifting; elasticity of taxable income; owner-managers; closely held business; dividend taxation; capital gains